SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN BERPRESTASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING DI LINGKUNGAN UNIVERSITAS LAMPUNG - Didik Kurniawan; Wamiliana Wamiliana; Rizqi Chandra Aditya (Jurnal Komputasi, 2015)
The selection of good achievement lecturers is a recognition for those lecturers who already had been conducting three principles of higher education with very good results. The selection of those lecturers in The University of Lampung is conducted annually. In the process of selection, the university will appoint assessing team to conduct assessments to the candidates. However, this assessment process is still conducted manually so that it will take a time to process the data. In addition, the assessment is still subjective in nature and is not yet relevant to the real conditions. Based on this background, the objective of this research was to build a decision support system to use in conducting selection process of good achievement lecturers in The University of Lampung. This decision support system was built based on web by using PHP programming language and MySQL as database, and Simple Additive Weighting method for making the decision. This method was used to determine point values of each criterion, and then ranked score was made to determine the best solution. The testing of the application using black box showed that this system was able to run properly. The results also influence the academic atmosphere and institutional quality.Â Keywords: decision support system, selection of good achievement lecturers , simple additive weighting